International Community Development: Edukasi IMS dan HIV/AIDS pada Remaja Santri di Pondok Pesantren, Johor Bahru, Malaysia - Bilah, Aisah Nur Ana; Nadzifah, Yasmin; Yamani, Laura Navika; Khairunisa, Siti Qamariyah; Indriati, Dwi Wahyu; Dinana, Zayyin; Manas, Nor Hasmaliana Abdul; Fuzi, Siti Fatimah Zaharah Mohamad; Ya’akob, Harisun; Aman, Nor Farahiyah; Yusoff, Nor Ida Madiha (Bahasa Indonesia, 2025)
Community development programs have the potential to enhance adolescents' awareness of the risks associated with sexually transmitted infections (STIs) and the preventive measures that can be taken to mitigate those risks, including HIV/AIDS. The International Community Development program was organized by the Research Centre on Global Emerging and Re-emerging Infectious Diseases (RC-GERID) of Universitas Airlangga. The topic of the program was the prevention of  STIs and HIV/AIDS among adolescent boarding school students. The objective of this activity is to enhance the student's knowledge and comprehension of STIs and HIV/AIDS, as well as the measures that can be taken to prevent the transmission of infectious diseases. The participants were 100 Madrasah Tahfidz Al-Quran An-Nur students in Johor Bahru, Malaysia. The methodology employed in this activity comprised pre-test and post-test questionnaires completed by participants, lectures, question-and-answer sessions, and discussions. The results demonstrated a statistically significant increase in knowledge and understanding of STIs, HIV/AIDS, and infection prevention among adolescent students, with an average increase of 22.0% in pre-test and post-test scores. This indicates that the educational material was effectively conveyed to the participants. The activity was conducted in an orderly, conducive, and interactive manner. Further community service with similar activities to be better than now   Abstrak Remaja merupakan kelompok yang rentan terhadap IMS dengan jumlah terbesar mengidap HIV/AIDS. Program pengabdian masyarakat dapat membantu meningkatkan kesadaran remaja tentang risiko dan langkah pencegahan penyakit IMS dan HIV/AIDS. International Community Development ini diselenggarakan oleh Research Center on Global Emerging and Re-emerging Infectious Diseases (RC-GERID) Universitas Airlangga, dengan topik pencegahan IMS (Infeksi Menular Seksual) dan HIV/AIDS pada remaja santri pondok pesantren. Tujuan kegiatan ini untuk meningkatkan pengetahuan dan pemahaman siswa mengenai IMS dan HIV/AIDS serta langkah pencegahan penyakit infeksi. Peserta kegiatan yaitu remaja santri di Madrasah Tahfidz Al-Quran An-Nur, Johor Bahru, Malaysia yang berjumlah 100 orang. Metode dalam kegiatan ini yaitu pengisian pre-test dan post-test oleh peserta, ceramah, tanya jawab dan diskusi. Hasil menunjukan bahwa adanya peningkatan pengetahuan dan pemahaman tentang IMS, HIV/AIDS, dan pencegahan infeksi pada remaja santri, dengan kenaikan nilai pre-test dan post-test sebesar 22,0%. Hal ini berarti materi edukasi tersampaikan dengan baik kepada peserta. Kegiatan berlangsung dengan tertib, kondusif, dan interaktif. Pengabdian masyarakat selanjutnya dengan kegiatan serupa agar lebih baik dari sekarang.